The Association between Growth and Neurodevelopment in Very Preterm Infants – A Follow-up Study in the PIPARI Study - Leppänen, Marika (Annales Universitatis Turkuensis D 1131, 2014)
Placental insufficiency is one major cause of intrauterine growth restriction and also relates to neurodevelopment. Preterm infants with very low birth weight are at risk of postnatal growth restriction as well as neurodevelopmental impairments. However, the optimal postnatal growth for long-term neurodevelopment is still unclear. The objective of this study was thus to investigate the association between growth and neurodevelopment in very preterm infants. The study populations consisted of 83 (I), 55 (II), 36 (III) and 181 (IV) infants with very low birth weight (below 1501 grams), and very or extremely low gestational age (below 32 and 26 weeks). Foetal blood circulation in relation to two-year neurodevelopment and the association between early growth and brain maturation at term age were studied. Postnatal growth, and its association with five-year cognitive outcome, was analysed. Changes in foetal blood circulation related to placental insufficiency associated with an adverse two-year cognitive outcome. Early postnatal growth in extremely preterm infants was comparable to a similar Swedish cohort. Preterm infants with slow intrauterine growth had less mature brains at term age; rapid catch-up growth until term age did not eliminate this difference. Weight gain and head circumference growth from birth until two years of age associated positively with five-year cognitive outcome in appropriate for gestational age infants. In small for gestational age infants, head circumference growth from term age to four months (corrected age) associated positively with their five-year cognitive outcome. The association between postnatal growth and neurodevelopment was different for prenatally normally grown versus slow grown preterm infants.

Istukan vajaatoiminta on yksi merkittävä syy sikiöajan kasvuhäiriölle ja on yhteydessä myös neurologiseen kehitykseen. Hyvin pienipainoisten keskosten syntymänjälkeinen kasvu ja myös neurologinen kehitys ovat riskissä häiriintymiselle. On vielä epäselvää minkälainen syntymänjälkeinen kasvu on optimaalinen neurologisen pitkäaikaisennusteen kannalta. Tämän tutkimuksen tavoitteena oli tutkia pikkukeskosen kasvun yhteyttä neurologiseen kehitykseen. Tutkimusryhmät koostuivat 83 (I), 55 (II), 36 (III), 181 (IV) hyvin pienipainoisista (syntymäpaino alle 1501 grammaa) sekä hyvin ja erittäin ennenaikaisista keskosista (raskausviikot alle 32 ja 26). Työssä tutkittiin sikiön verenkierron yhteyttä neurologiseen kehitykseen kahden vuoden iässä sekä varhaisen kasvun ja lasketun iän aivojen kypsyyden välistä yhteyttä. Syntymänjälkeistä kasvua tutkittiin ja selvitettiin sen yhteyttä älylliseen tasoon viiden vuoden iässä. Istukan vajaatoimintaan liittyvät sikiön verenkierron muutokset olivat yhteydessä huonompaan älylliseen tasoon kahden vuoden iässä. Erittäin ennenaikaisesti syntyneiden keskosten kasvu oli yhtenevä ruotsalaisen aineiston kanssa. Keskosilla, joilla sikiöaikainen kasvu oli ollut hidasta, oli aivojen kypsyminen jäljessä lasketussa iässä. Nopea kiinniottokasvu laskettuun aikaan mennessä ei korjannut tätä eroa. Raskausviikkoihin nähden normaalikokoisilla keskosilla syntymänjälkeinen kasvu kahteen ikävuoteen saakka oli positiivisessa yhteydessä älylliseen tasoon viiden vuoden iässä. Raskausviikkoihin nähden pienikokoisilla keskosilla ainoastaan pään kasvu lasketusta iästä neljän kuukauden (korjattuun) ikään saakka oli positiivisesti yhteydessä älylliseen tasoon viiden vuoden iässä. Syntymänjälkeisen kasvun ja neurologisen kehityksen välinen yhteys oli erilainen sikiöaikana normaalisti kasvaneiden ja hitaasti kasvaneiden keskoslasten välillä.